Pendampingan Pastoral Kepada Satu Pasangan Suami-Isteri Kristen Yang Belum Mempunyai Anak - Frans Rachman Silaban, Dulles; Simaremare, Julius Tumpak Marganda; Hasibuan, Ricky Pramono (JURNAL DIAKONIA, 2024)
Marriage is regarded as a divine command that binds a man and a woman together in one flesh to continue the lineage. However, for Christian couples who have yet to bear children, psychological and social pressures often weigh heavily. Through qualitative research, this article explores the experiences and challenges faced by Christian couples in Nagasaribu, Humbang Hasundutan. The research methodology involves direct interviews with the couples to understand their thoughts and feelings. The findings indicate that the presence of children is deemed crucial for the continuation of the lineage and inheritance. Pressures from family, society, and the church further complicate this situation. In conclusion, the researchers suggest that couples require intensive pastoral support tailored to their needs and desires. Meaningful pastoral care is necessary to assist them in facing these challenges. Therefore, this article highlights the importance of pastoral support in addressing the challenges of infertility and the inability to conceive within certain cultural and religious contexts.